Hubungan Lama Terapi Hemodialisis dengan Kualitas Hidup pada Pasien GGK di RS Mekar Sari Kota Bekasi - Futriani, Elfira Sri; Jailani, Hafiz (Universitas Malahayati, 2025)
ABSTRACT Chronic renal failure (CKD) is a pathophysiological condition caused by various factors, resulting in decreased kidney function. In 2013, it was recorded that 2 out of 1000 people or 499,800 people in Indonesia experienced CKD. In sufferers of chronic kidney failure, the body is weakened and dependent on dialysis machines. The quality of life of patients with chronic kidney disease undergoing hemodialysis is poor, the analysis shows that the factors that influence the quality of life of patients with chronic kidney disease undergoing hemodialysis. To determine the relationship Length of Hemodialysis Therapy and Quality of Life in CKD Patients at Mekar Sari Hospital, Bekasi City in 2025. This research uses a quantitative research approach with a correlational design which aims to understand the relationship between variables. Cross-sectional method. Results: Chi-Square test results show a significance (p) value of 0.038 (p < 0.05), which means there is a significant relationship between the duration of hemodialysis and the patient's quality of life. There is a relationship between the duration of hemodialysis therapy and the quality of life in CKD patients at Mekar Sari Hospital, Bekasi City in 2025. It is hoped that the results of this research will provide understanding for families so that they can increase family support and quality of life so that patients do not feel bored with their families who suffer from hemodialysis therapy. Keywords: Chronic Kidney Failure, Hemodialysis Therapy, Quality of Life. ABSTRAK Gagal ginjal kronik (GGK) adalah kondisi patofisiologi yang disebabkan oleh berbagai faktor, mengakibatkan penurunan fungsi ginjal. Pada tahun 2013, tercatat 2 dari 1000 orang atau sebanyak 499.800 orang di Indonesia mengalami CKD.Pada penderita gagal ginjal kronik kondisi tubuh yang melemah dan ke tergantungan pada mesin-mesin dialysis. Kualitas hidup pasien penyakit ginjal kronik yang menjalani hemodialisis buruk, dari analisis menyatakan bahwa faktor-faktor yang mempengaruhi kualitas hidup pasien penyakit gagal ginjal kronik yang menjalani hemodialisa. Untuk mengetahui Hubungan Lama Terapi Hemodialisis Dengan Kualitas Hidup Pada Pasien GGK DI RS Mekar Sari Kota Bekasi Tahun 2025. Penelitian ini menggunakan pendekatan penelitian kuantitatif dengan desain korelasional yang bertujuan untuk memahami hubungan antara variabel. Metode cross-sectional. Hasil uji Chi-Square menunjukkan nilai signifikansi (p) value sebesar 0,038 (p < 0,05), yang berarti terdapat hubungan yang signifikan antara lama hemodialisis dan kualitas hidup pasien. Terdapat Hubungan Lama Terapi Hemodialisis Dengan Kualitas Hidup Pada Pasien GGK DI RS Mekar Sari Kota Bekasi Tahun 2025. Diharapkan hasil penelitian ini memberikan pemahaman bagi keluarga sehingga dapat meningkatkan dukungan keluarga serta kualitas hidup agar pasien tidak merasa bosan terhadap keluarga yang menderita terapi hemodialisis. Kata Kunci: Gagal Ginjal Kronik, Terapi Hemodialisis, Kualitas Hidup